Molecular identification and ochratoxigenic potential of black Aspergillus from various substrates and indoor environment - Wardah Abdul Rahman,; Latiffah Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Aspergillus section Nigri or black Aspergillus is characterized by dark brown to black colonies. Several species of this group showcase the ability to produce ochratoxin A (OTA), contaminating various types of food and feed. This study was conducted to identify black Aspergillus isolated from rice, groundnuts, spices, corn grains, soil, and indoor environment and determine the ability of the isolates to produce OTA. Based on ITS, β-tubulin and calmodulin sequences, 177 isolates of black Aspergillus from various substrates and indoor environment were identified as A. niger, A. aculeatus, and A. tubingensis. By using two sets of primers to amplify two ochratoxin biosynthesis genes (PKS15KS and PKS15C-MeT genes), the OTA genes were detected in only six A. niger isolates from rice and indoor environment. These six A. niger isolates produced 8 to 308 μg/g of OTA as quantified using UPLC analysis. No OTA gene was detected in any of the A. tubingensis and A. aculeatus isolates. In conclusion, three black Aspergillus species, A. niger, A. aculeatus, and A. tubingensis, were identified from rice, groundnuts, spices, corn grains, soil, and indoor environment. Only six isolates of A. niger produced OTA indicating most of the A. niger isolates were non-OTA producers. These results could thus portray the occurrence of OTA in the field. Since both the number of isolates producing OTA and the levels of OTA production were low, it could be possibly assumed that the occurrence as well as the levels of OTA in the field are also low.